Transformational Leadership of School Principals in Developing Teacher and School Achievement - Naimatuz Zahriyah; Imam Fuadi (World Journal of Islamic Learning and Teaching, 2026)
Leadership is the key to success in educational institutions, transformational leadership always emphasizes the vision, mission, and goals of the institution and motivates all school members to cooperate in advancing the institution. Transformational leadership implemented at SMAN 2 and MAN 2 Kediri City is able to bring positive changes and encourage better achievements. Educational institutions whose leaders implement transformational leadership tend to be more active and adaptive to change. This research model uses a qualitative approach with a multi-case study design. Data collection techniques use in-depth interviews, participant observation, and documentation. Data analysis techniques use condensation, data display, and drawing conclusions. The findings are that the principal drives teacher professionalism by encouraging followers to imitate his positive behavior, be flexible, and form a personal commitment to organizational transformation. The principal acts as an inspiring motivator by providing inspirational motivation, building effective communication, and consolidating the strength of followers to support transformation.Principals hone teachers' intellectual abilities by involving them in decision-making, preparing them for challenges, and providing coaching, feedback, and evaluation. Principals act as role models by providing personal feedback, rewarding them, and promoting the achievement of the institution's goals.